Quantifying Remission Probability in Type 2 Diabetes Mellitus - Kalra, Sanjay; Bantwal, Ganapathi; Kapoor, Nitin; Sahay, Rakesh; Bhattacharya, Saptarshi; Anne, Beatrice; Gopal, Raju A; Kota, Sunil; Kumar, Ashok; Joshi, Ameya; Sanyal, Debmalya; Tiwaskar, Mangesh; et al. (Clinics and practice, 2021)
Type 2 diabetes mellitus (T2DM) is a chronic progressive disorder and is associated with significant morbidity and mortality. The concept of T2DM remission and the reversal of diabetic parameters to normal levels has been gaining momentum over the past years. T2DM remission is increasingly being recognized by various global guidelines. Multiple models have been developed and validated for quantifying the extent of remission achieved. Based on favorable clinical evidence, T2DM remission can be considered as the therapeutic goal in diabetes management and, in select cases, as an alternative to expensive treatment options, which can be burdensome as T2DM progresses. This narrative review discusses the available strategies, such as lifestyle interventions, physical activity, bariatric surgery, medical nutrition therapy, and non-insulin glucose-lowering medications, for achieving T2DM remission. Although the concept of T2DM remission has emerged as a real-world option, effective implementation in routine clinical practice may not be feasible until long-term studies prove the efficacy of different approaches in this regard.